Parvimonas micra: A rare cause of native joint septic arthritis. (June 2016) - Baghban, Adam; Gupta, Shaili
Abstract: Parvimonas micra is a fastidious, anaerobic, gram positive coccus, which is found in normal human oral and gastrointestinal flora. It has also been known as Peptostreptococcus micros and Micromonas micros with its most recent re-classification in 2006. It has been described in association with hematogenous seeding of prosthetic joints[1, 2] . Several cases of discitis and osteomyelitis have been described in association with dental procedures and periodontal disease often with a subacute presentation. However, cases of native joint septic arthritis are limited[3–5] . Per our literature review, there is one case of native knee septic arthritis described in 1999, with a prolonged time to diagnosis and treatment due to difficulty culturing P. micra. The previously reported patient experienced significant joint destruction and morbidity[6] . Advances in culture techniques and new methods of organism identification including MALDI-TOF and 16s rRNA sequencing have lead to increased identification of this organism, which may be a more frequent bone and joint pathogen than previously realized.